Impact of Initial Shunt Type on Echocardiographic Indices in Children After Single Right Ventricle Palliations: The SVR Trial at 6 Years. (February 2019) - Frommelt, Peter C.; Hu, Chenwei; Trachtenberg, Felicia; Baffa, Jeanne Marie; Boruta, Richard J.; Chowdhury, Shahryar; Cnota, James F.; Dragulescu, Andreea; Levine, Jami C.; Lu, Jimmy; Mercer-Rosa, Laura; Miller, Thomas A.; et al.
Abstract : Background: Heart size and function in children with single right ventricle (RV) anomalies may be influenced by shunt type at the Norwood procedure. We sought to identify shunt-related differences during early childhood after staged surgical palliations using echocardiography. Methods: We compared echocardiographic indices of RV, neoaortic, and tricuspid valve size and function at 14 months, pre-Fontan, and 6 years in 241 subjects randomized to a Norwood procedure using either the modified Blalock-Taussig shunt or RV-to-pulmonary-artery shunt. Results: At 6 years, the shunt groups did not differ significantly in any measure except for increased indexed neoaortic area in the modified Blalock-Taussig shunt. RV ejection fraction improved between pre-Fontan and 6 years in the RV-to-pulmonary artery shunt group but was stable in the modified Blalock-Taussig shunt group. For the entire cohort, RV diastolic and systolic size and functional indices were improved at 6 years compared with earlier measurements, and indexed tricuspid and neoaortic annular area decreased from 14 months to 6 years. The prevalence of ≥moderate tricuspid and neoaortic regurgitation was uncommon and did not vary by group or time period. Diminished RV ejection fraction at the 14-month study was predictive of late death/transplant; the hazard of late death/transplant when RV ejection fraction was <40% was tripled (hazard ratio, 3.18; 95% CI, 1.41–7.17). Conclusions: By 6 years after staged palliation, shunt type has not impacted RV size and function, and RV and valvar size and function show beneficial remodeling. Poor RV systolic function at 14 months predicts worse late survival independent of the initial shunt type. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00115934. Abstract : Supplemental Digital Content is available in the text.